Revitalization of Islamic Religious Education and Ethics in Primary and Secondary Schools in the Era of Industrial Revolution 4.0 - Darojat, Jajat; Yusuf, Iqbal Anggia; Asyari, Hobir; Ruswandi, Uus; Arifin, Bambang Samsul (Eduprof : Islamic Education Journal, 2025)
The changing times and developments in the era of the Industrial Revolution 4.0 bring significant opportunities and challenges to people's lives, including education. This era is marked by rapid developments in digital technology, artificial intelligence, big data, and the Internet of Things (IoT), which are changing the mindset, learning methods, and social interactions of students. Education is no longer limited to physical classrooms, but has expanded into the digital realm, requiring teachers, curricula, and learning systems to adapt quickly and effectively. Moreover, Islamic Religious Education must be able to adapt and not be antipasti to the changes and developments of the times. By integrating digital technology into the learning process, using social media as a means of preaching, and developing a curriculum that is relevant to contemporary issues such as digital ethics and environmental sustainability, all based on Islamic values. The purpose of this study is to examine in depth how the revitalization of Islamic Religious Education and Ethics can be carried out to remain relevant and effective in facing the challenges of the 4th Industrial Revolution era. To achieve this objective, this study employs a qualitative approach using library research methods, which involves analyzing literature from various relevant scientific sources, such as journals, books, and official documents. From the results of the study that in facing the challenges of the Industrial Revolution 4.0 requires steps in dealing with it, namely; 1). increasing the competence of Islamic Religious Education teachers, 2). relevant curriculum development, 3). collaboration between religious education and technology, 4). character education in a global context. In the face of these developments, education must also be able to change the paradigm of education. That students are autonomous subjects, who are involved in learning activities. The cooperation of various elements such as family and society is also needed in an effort to revitalize Islamic religious education and character education. Because this effort requires effective collaboration and integration between religious education, technology and ethics.